2019
DOI: 10.1177/0022034519843487
|View full text |Cite
|
Sign up to set email alerts
|

Fluoridated Water Modifies the Effect of Breastfeeding on Dental Caries

Abstract: Breastfeeding is important for health and development. Yet, the interaction between breastfeeding duration and usage of fluoridated water on caries experience has not been investigated. This study examined exposure to fluoridation as an effect modifier of the association between breastfeeding duration and caries. The 2012 to 2014 national population-based study of Australian children involved parental questionnaires and oral epidemiological assessment. Children were grouped by parent-reported breastfeeding dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 25 publications
2
23
0
Order By: Relevance
“…After all, the high cariogenicity of bottle feeding has also been confirmed by many studies [32]. One recent study has contributed evidence for the nonlinear association between breastfeeding duration and ECC and the auxiliary role of fluoridated water in reducing the negative effects of feeding on ECC [33]. This finding reminds us that more relevant variables need to be considered in future studies to elucidate the correlation between feeding methods and ECC.…”
Section: Logistic Regression Analysesmentioning
confidence: 58%
See 1 more Smart Citation
“…After all, the high cariogenicity of bottle feeding has also been confirmed by many studies [32]. One recent study has contributed evidence for the nonlinear association between breastfeeding duration and ECC and the auxiliary role of fluoridated water in reducing the negative effects of feeding on ECC [33]. This finding reminds us that more relevant variables need to be considered in future studies to elucidate the correlation between feeding methods and ECC.…”
Section: Logistic Regression Analysesmentioning
confidence: 58%
“…Limitations of the study include the issues related to the OHC knowledge and attitude items designed for the questionnaire being relatively basic and traditional. Several major risk factors have been incorporated into the current study, unlike the monographic studies that have excavated and explored sufficient detailed information about one certain targeting factor associated with ECC [29,33,52]. We also have to acknowledge that some data on detailed information is limited, such as the frequency of bedtime feedings, brushing efficiency, floss assistance status, and cariogenic microbial flora, each of which is reported to be associated with ECC.…”
Section: Logistic Regression Analysesmentioning
confidence: 99%
“…After all, the high cariogenic of bottle feeding has also been confirmed by many studies [30]. One latest research contributes evidence for the nonlinear association between breastfeeding duration and ECC and the auxiliary role of fluoridated water in reducing the negative effects of feeding on ECC [31]. That reminds us more relevant variables need to be considered in future studies to elucidate the correlation between feeding methods and ECC.…”
Section: Logistic Regression Analysesmentioning
confidence: 70%
“…Limitations include the issues in the OHC knowledge and attitude designed for the questionnaire 15 are relatively basic and traditional. Several major risk factors are incorporated in current study, but unlike those monographic researches which excavated and explored sufficient detailed information about one certain targeting factor associated with ECC [27,31,50]. We have to say that some data on detailed information is limited, such as frequency of bedtime feeding, brushing efficiency, floss assist status, cariogenic microbial flora, each of which is reported to be associated with ECC.…”
Section: Logistic Regression Analysesmentioning
confidence: 99%
“…The evidence however, is limited and inconsistent, with some studies finding an association only if breastfeeding continued beyond 18 or 24 months. Furthermore, a recent national study from Australia demonstrated that sustained breastfeeding (> 24 months) was not associated with ECC amongst children exposed to fluoridated water (Ha et al, 2019), indicating that the use of fluoridated water early in life moderated the relationship. The purpose of this presentation is to 1) critique the evidence related to breastfeeding practices and ECC; and 2) report the findings of an investigation into the effects of breastfeeding duration and night-time breastfeeding on ECC amongst a cohort of Australian toddlers.…”
Section: Best Beginningsmentioning
confidence: 99%